Tim Tyler's adventures - Young, Lyman; Young, Bob, (Cartoonist); Chatto, Keith, 1924-1992; Musial, Joseph W., 1905-1977; Sagendorf, Bud (Surry Hills, N.S.W. : Page Publications, 1965)
Includes companion pieces such as: Henry ; The Katzenjammer kids / by Joe Musial ; Thimble Theatre starring Popeye / Bud Sagendorf.
Cover title.
"Page silver star comics" -- Cover.
Covers and introductory frames drawn by Australian comic artist, Keith Chatto.
Issues 15 (1964) to 20 (1965) of Tim Tyler's adventures were published by Photo-Type Press.
Description based on: No. 22 (1965)
Keywords: Jungle survival -- Comic books, strips, etc; Jungle survival -- Periodicals; Adventure and adventurers -- Comic books, strips, etc; Adventure and adventurers -- Periodicals; Australian; Comic books, strips, etc